EFFECTS OF GERMINATION TIME AND DRYING TEMPERATURE ON CHEMICAL AND SENSORY QUALITY OF FINGER MILLET FLOUR - Gautam, Navin; Acharju, Binu; Karki, Dhan Bahadur; Karki, Prapti (Food and Feed Research, 2026)
This study was aimed to determine the effect of germination time and drying temperature on chemical and sensory quality of finger millet flour. Finger millet was collected were cleaned and soaked in water overnight at room temperature and strained then spread over the muslin cloth. The germination was carried out at room temperature  for 24, 48 and 72 h and then dried in a cabinet dryer at 80, 90 and 100  and then milled using pulp grinder. The effect of germination time and drying temperature on TPC, antioxidant activity, glucose content, reducing sugar and total sugar were analyzed. The samples were subjected to sensory evaluation in terms of color, smell, taste, flavor and overall acceptance. The moisture content, crude protein, crude fat, total ash, crude fiber, carbohydrates, iron and calcium content of raw finger millet was found to be 14.6%, 7.3%, 1.753%, 3.29%, 3.9%, 69.157%, 12.8 mg/100g and 370.03 mg/100g respectively on dry basis except for moisture. The glucose content, reducing sugar and total sugar was found to be significantly highest for millet flour germinated for 72 h and dried at 80   in cabinet drier while TPC and antioxidant activity was slightly lower. From sensory analysis, the mean sensory score of 48 h germinated and dried at the 90   in cabinet drier flour was higher of all the samples. The crude protein, crude fat, crude fiber, iron and calcium content increased significantly; moisture and total ash decreased significantly.
Keywords: Germination, drying, composition, sensory analysis